Análisis e interpretación a los estados financieros en la fundación Àlvarez de la ciudad de Loja periodo: 2014-2015. - Salinas Minga, Yesenia Mercedes (2018)
When carrying out the present work of Analysis and Interpretation to the Financial Statements of the periods 2014-2015, it was carried out in compliance with the Regulation of Academic Regime of the National University of Loja as a prerequisite to choose the Degree of Engineering in Accounting and Auditing. Likewise with the purpose of providing the Alvarez Foundation with a proposal for economic and financial improvement and in relation to making timely decisions. The present study of Financial Analysis in the Álvarez Foundation was developed in compliance with the objectives proposed in the research project, that is why the application of vertical and horizontal analysis to the Financial Statements was made allowing the comparison of each of the accounts of the balance sheets and results, determining increases and decreases between one period and another. The application of the financial indicators facilitated the knowledge of the liquidity, solvency and indebtedness capacity that the company has in the periods under study. Finally, it can be concluded that the total development of the Analysis and interpretation of the financial statements of the Alvarez Foundation was carried out in 2014 and 2015 based on vertical and horizontal analysis as well as the application of indexes or financial indicators. Therefore, it is recommended that this work be taken into account so that its managers can make the best decisions.